Science Structure as A Scientific Method Concept (The Teaching of Elementary-Age Children) - Salminawati, Salminawati; Ningsih, Titik (Jurnal Basicedu, 2022)
Science is knowledge or a set of conceptions, principles, laws, and philosophies that are formed through the scientific method (systematic). The systematic method includes a continuous process of observation and experimentation. This study aims to describe the structure of science as a concept of the scientific method. The focus is teaching for elementary age children. This type of research is a qualitative approach with a literature study method. Sources of data and analysis materials based on scientific references from credible pages, Google Scholar, DOAJ, and Sinta. The results of this study indicate that the scientific structure in science learning helps children to think systematically and logically in observing and experimenting with nature. Through this research, it is understood that there are 5 (five) elements in educating children about the structure of science as the concept of the scientific method, namely identification of targets, format of statements, variety of statements, main functions, and systematic structures.